IMPROVING THE EFFICIENCY OF RAPID FILTERS AT WASTEWATER TREATMENT FACILITIES FOR WATER - , Е. П. (Municipal economy of cities. Series: «Economy science», 2013)
A method of improving the efficiency of fast filters with the use of flocculants and PAA Magnafloc LT 25 in the processes of water treatment facilities for water